Development of Thematic Teaching Materials Based on Discovery Learning in Elementary School - Nur Wahyuni; Lala Jelita Ananda (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2021)
The purpose of this research is to develop teaching materials using the discovery learning model to improve thematic learning outcomes in elementary schools. This research aims to develop thematic teaching materials based on the discovery learning model for fourth grade students of elementary school and to describe the feasibility of thematic teaching materials products based on the discovery learning model. This type of research is research and development (R&D). The development model used is the ADDIE (Analysis, Design, Develop, Implementation and Evaluate) model. The results of research on thematic teaching materials based on discovery learning are from the results of assessments carried out by media experts, material experts and students' responses during field trials. The results of the validation show that the overall score is 3.7 so that it is included in the